Evidence-Based Prevention: Community and Individual Approaches (Out of Print) - Kristi Ferguson (Association of American Medical Colleges, 2006)
Abstract This PowerPoint presentation reviews the top 10 causes of mortality in the United States, discusses factors contributing to those causes, describes current recommendations regarding community-based interventions, and considers recommended approaches for individual physicians. Associated handouts include a written version of the PowerPoint, a table of recommended preventive services, and a chart of the top 10 causes of death per age group for 2002. An earlier version of this presentation was delivered to first-year students and was well received. When the class was asked about the most important things learned in the presentation, a significant proportion mentioned public health concepts. The presentation can incorporate interactive activities: (1) Ask students to review the handout chart of the top 10 causes of death and describe what they find interesting or surprising, and (2) at the conclusion of the lecture, ask students to discuss interventions not on the recommended list and consider why these may be absent.